Analysis of BAI' Muzayadah in the Auction of Collateral Items at the State Property and Auction Services Office (KPKNL) - Imamah, Ayu Nur; Semaun, Syahriyah; Muliati, Muliati; Islamulhaq, Islamulhaq; Bahri, Andi (Jurnal Ilmu Manajemen Profitability, 2025)
This study analyzes Bai’ Muzayadah in the auction of collateral assets at KPKNL Parepare. The objective of this research is to examine the implementation of collateral asset auctions at KPKNL Parepare based on the principles of Bai’ Muzayadah in Islamic economics and the collateral asset auction system from the perspective of Islamic economic law.  The research employs a descriptive qualitative method, categorized as field research. Data sources include primary data obtained through direct interviews at KPKNL Parepare and secondary data such as books, journals, and articles relevant to the topic. Data analysis techniques involve data collection, data reduction, data presentation, and conclusion drawing. The validity of the data is tested using source triangulation, technique triangulation, and time triangulation. The findings indicate that (1) the implementation of collateral asset auctions at KPKNL Parepare, from the perspective of Islamic economics, utilizes internet-based methods (e-auction) through open bidding and closed bidding systems. These systems incorporate mechanisms such as security deposits and minimum bidding limits. (2) The application of Islamic economic principles, including justice, transparency, and voluntary agreements in the auction process, aligns with the principles of transparency, legal certainty, and efficiency. Auction announcements are made via the website and leaflets. The auction process is conducted thoroughly to minimize errors, beginning with the preparation stage, auction determination, payment of participants’ security deposits, and the transfer of ownership or auction minutes as legal proof for the winning bidder. These practices are consistent with Islamic economic law principles and aim to promote societal welfare.